Halomonas fontilapidosi sp. nov., a moderately halophilic, denitrifying bacterium - González-Doménech, Carmen María; Martínez-Checa, Fernando; Quesada, Emilia; Béjar, Victoria (Microbiology Society, 2009)
We have made a polyphasic taxonomic study of strain 5CR(T), isolated from Fuente de Piedra, Málaga, southern Spain. The strain is a moderately halophilic, Gram-negative rod, oxidase-positive and motile by a single polar flagellum. It does not produce acids from sugars and shows respiratory metabolism, using oxygen, nitrate and nitrite as terminal electron acceptors. It requires NaCl and grows best with 5-7.5 % w/v at temperatures of between 32 and 45 degrees C within a pH range of 6-8. Its 16S rRNA gene sequence indicates that strain 5CR(T) belongs to the genus Halomonas in the class Gammaproteobacteria. Its closest relatives are Halomonas alimentaria, H. nitroreducens, H. shengliensis and H. ventosae, with the type strains of which our strain showed 16S rRNA gene sequence similarity values of 96.7-97.8 %. DNA-DNA hybridization studies between strain 5CR(T) and H. ventosae CECT 5797(T), the phylogenetically nearest type strain, showed 40 % relatedness. Its G+C content is 65.7 mol%. Its major fatty acids are C(18 : 1)omega7c (31.36 %), C(16 : 0) (25.55 %), C(16 : 1)omega7c/iso-C(15 : 0) 2-OH (23.23 %), C(19 : 0) cyclo omega8c (8.14 %), C(12 : 0) 3-OH (5.76 %) and C(10 : 0) (2.22 %) and the predominant respiratory lipoquinone is ubiquinone with nine isoprene units (Q-9). The proposed name for the novel species is Halomonas fontilapidosi sp. nov., strain 5CR(T) (=CECT 7341(T) =LMG 24455(T)) being the type strain.
Keywords: Microorganismos halófilos; Bacterias desnitrificantes; Halomonas; Halophilic; Denitrifying